Analisis Faktor-Faktor Kesulitan Belajar Bahasa Arab Kelas V Yahya SDIT Permata Bunda II Teluk Betung Bandar Lampung - Rina Wati; Langgeng Sutopo; Rima Ajeng Rahmawati (Program Studi Pendidikan Bahasa Arab, 2021)
This research is motivated by learning Arabic for the fifth grade students of SDIT Permata Bunda II Teluk Betung Bandar Lampung. Where students still have difficulty in learning Arabic, This study uses a qualitative descriptive approach that aims to analyze the factors of learning difficulties in Arabic. This study uses a qualitative descriptive approach that aims to analyze the factors of learning difficulties in Arabic. The subject of this research is the fifth grader Yahya SDIT Permata Bunda II Teluk Betung Bandar Lampung in the 2020/2021 academic year. with a total of 27 students. This data collection technique uses interviews, observations, documentation, and questionnaires. Data analysis was carried out by descriptive analysis. The results of this study indicate that the difficulty of learning Arabic at SDIT Permata Bunda II is grouped into two, namely internal factors and external factors. Where students have difficulty learning Arabic regarding internal factors, namely students find it difficult to understand Arabic lessons and the assumption that Arabic is a difficult language to learn, External factors that cause student learning difficulties can be found in the family environment which consists of a lack of attitude and encouragement to learn, lack of parental support for Arabic lessons, mother tongue and environmental factors and lack of student motivation.